Investigating the Students’ Perceptions towards the Use of Online Learning Application in Learning English - Robi Sugara (Research in English and Education Journal, 2023)
This study investigated the EFL Students’ perceptions and the challenges they encountered while dealing with the Covid-19 epidemic. This study falls under the category of descriptive qualitative research, and questionnaires were used to gather data and information from respondents. The research revealed that despite the Covid-19 outbreak, students had a positive perspective of online education. The majority of participants concur that using online learning applications like Zoom Meeting, Edmodo, Google Classroom, and WhatsApp Group is the best option for conducting coursework digitally. The pupils also concurred that Zoom is the preferred and most advantageous application for carrying out online studying in the middle of the Covid-19 pandemic. As for the challenges, some students still struggle to complete the online application since they don’t have a firm grasp of technology. They frequently struggle to understand the menus and functions of the application. When using those tools, the slight negative perception of online learning was also emotionally influenced. The researcher advised studying or understanding how to use specific online learning applications because they are very beneficial for both online study and virtual meetings at work.